Anonimato del Donante y Derecho a Conocer: un Difícil Equilibrio (Donor Anonimity and Right to Know: a Challenging Balancing) - Itziar Alkorta Idiakez; Esther Farnós Amorós (Oñati Socio-Legal Series, 2015)
This article examines the tension among the anonymity of the gamete donor and the right of the child to know his origin, following the latest trend of the European legal systems. The analysis of legal systems that recognize such a right to children conceived through donated gametes allows us to think further on the hypotheses, now more extended, which consider that traditional arguments for secrecy are out-dated. In this regard, the article also challenges the different treatment granted to adopted children and donor gamete children by legal systems such as the Spanish one. Beyond the possible conflicting rights of children, donors and parents, arguments provided by anonymity supporters, such as moral damages resulting from disclosure or the possible link between disclosure and the decrease in the number of donors, should be also taken into account. However, these arguments require absolute empirical evidence which is not currently conclusive. Alternatively, disclosure of the identity of the donor, once the child has reached enough maturity, is seen as a solution to be studied in detail, as long as it does not lead to the establishment of parentage links. The article suggests that this solution is consistent with the needs of donor families, and with a major trend in family law supporting the right to know one’s genetic origin, dissociated from biological and legal parentage spheres.